INFLUENCE OF INSTRUCTIONAL MEDIA ON THE TEACHING-LEARNING OF MUSIC EDUCATION - Adesipe Muyiwa; Omotayo Abidemi (Galaxy International Interdisciplinary Research Journal, 2022)
This paper gave an insight into what influence of instructional media on the teaching-learning of music education in schools in Nigeria is. This paper examined the history of music education in Nigeria which was dated back to 1842 when music began as a subject of study in Nigeria. The powerful role of music in the society was vividly discussed to show its contribution to our society. The paper concluded by looking into the influence of instructional media on the teaching learning of music education in schools.